An Analysis of Illness Intervention: Basis for Enhanced Nursing Intervention Process - Agpawan, Zenaida C. (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examined the utilization of the nursing process by the school nurse at the University of Baguio Laboratory Elementary School for the school year 2022-2023. The nursing process is the foundation for providing quality and professional nursing care which the researcher scrutinized by reviewing pertinent health records of students. Documents revealed that the school nurse lacked documentation on two important steps in the nursing process which were the plan of care and the evaluation phases, the rest of the processes were satisfactorily met.